A study on waste generation in commercial area at Indera Mahkota 5, Kuantan, Pahang - Kew Hong, Soo (2013)
Solid waste is anything that been consume and discards from human's activities on their daily life. These waste also known as trash, garbage, refuse and rubbish. Increasing of solid waste production in commercial is one of the government concerns especially in Kuantan. In order to reduce and handle the solid waste, suitable methods must be chose for their efficiency and effectiveness. This research was focus on solid waste composition and solid waste generation rate in Indera Mahkota 5 commercial area. The commercial premises were divided into three categories: public, service and product with 15 participants. For this study, two methods of data gathering were applied: on site sampling involving weigh and segregate solid waste generated and questionnaire distribution. The relationship between solid waste composition and solid waste generation is based on type of the premise. Each premise generated different type of waste with different generation rate. Factors of waste generation also affect the waste composition and waste generation in commercial area. For public type service, the total sample weight is 44.80 kg. /From the total sample weight, it consists 33 kg of food waste, 1.15 kg of paper, 6.90 kg of plastic and 3.75 kg of tin/can/metal/aluminum. For service type premise, the total sample weight is 26.56 kg. From the total sample weight, it consists 9.29 kg of food waste, 4.03 kg of paper, 6:89 kg of cardboard, 6.08kg of plastic, 0.20 kg of tin/can/metal/aluminum and 0.07 kg of other waste. For the product type premise, the total sample weight is 1009.64 kg. There are 892.07 kg of food waste, 23.07 kg of paper and 15.93 kg of cardboard, 0.05 kg of wood, 65.61 kg of plastic, 11.26 kg of tin/can/metal/aluminum and 1.65 kg of other wastes.